A Typology of Humor in Business Signage in Padang City: A Linguistic Landscape Approach - Handayani, Mita; Oktavianus, Oktavianus; Zulprianto, Zulprianto (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study investigates the typology of Indonesian humor represented on business signboards and banners in Padang City through a linguistic landscape perspective. The research applies Humor Theory, particularly Raskin’s Semantic-Script Theory of Humor (1984), and Kress and Leeuwen’s Visual Grammar Theory (2006) to examine both linguistic and non-linguistic elements of humor. A qualitative-descriptive method was employed to enable an in-depth analysis of the data. Data were collected through field observation by photographing humorous signboards and banners across business areas in Padang City. Total sampling was applied, and Mahsun’s MPE framework was used for data analysis. The findings reveal that humor is expressed through both linguistic and visual elements. Linguistically, humor appears in three units: words, phrases, and sentences, with sentences being the most dominant form, accounting for 63.63% on signboards and 60.71% on banners. Non-linguistically, humor is represented through visual features such as text color, background color, and spatial placement. Humor most frequently appears in black text on a white background on signboards and in white text on a yellow background on banners. In terms of layout, humorous elements are commonly positioned at the bottom of signboards and at the center of banners. These findings highlight how humor in business signage is constructed through a combination of linguistic structures and visual design within the linguistic landscape.